A deliberately emergent strategy – a key to successful city branding. Issue 2 (13th July 2015) - Lindstedt, Janne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to address a neglected issue in the literature on place brand co-creation, namely, the strategic planning of the branding process. Furthermore, the paper demonstrates the benefits of a deliberately emergent strategy. Design/methodology/approach – A qualitative case study focusing on Turku, Finland, supports the development of the argument. In this study, branding of Turku is examined both during the European Capital of Culture 2011 (ECoC) project and after it. Findings – The contribution of the ECoC 2011 project – which was widely perceived as a success – to Turku's brand was based on a deliberately emergent strategy. Afterwards, the local government has, however, chosen a different approach to branding. Research limitations/implications – Given the increasing popularity of brand thinking among practitioners all over the world, it would be meaningful for scholars to pay more attention to the application of brand co-creation in place branding strategies. Practical implications – The deliberately emergent branding strategy could be considered an approach to applying the idea of brand co-creation in practice. It enables local stakeholders to make their voices heard and results in increased credibility of a branding process. Originality/value – Place brand co-creation has not yet been examined from strategic planning's point of view. The need for this kind of examination is apparent, because branding strategies have traditionally been based on the idea of static place identity. The Turku case helps to propose a solution in terms of the notion of deliberately emergent branding.